Collaborative Dynamics Pemberian Makanan Tambahan Lokal dalam Upaya Percepatan Penurunan Stunting di Kelurahan Kalijaga Kota Cirebon - Bayu Dwi Putri, Agustina; Bekti, Heriijanto (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
Stunting is still a major health problem in Indonesia, including in Cirebon City, which can have an impact on the quality of human resources in the future. The government has adopted various policies to accelerate stunting reduction, one of which is through a collaborative governance approach, which emphasizes multi-actor involvement in program implementation. This research aims to analyze the dynamics of collaboration in implementing the Supplementary Feeding Program (PMT) as part of efforts to accelerate stunting reduction in Kalijaga Village, Harjamukti District, Cirebon City. By using a qualitative approach and case studies, this research refers to the collaborative governance dynamics theory of Emerson et al. (2011), which includes the dimensions of mobilizing shared principles, shared motivation, and capacity for joint action. Research results show that even though a collaborative forum has been formed with the roles of various stakeholders, there are still several obstacles in planning, the effectiveness of cadre roles, as well as monitoring and evaluating program implementation. Therefore, strengthening coordination and synergy between actors is a strategic step to increase the effectiveness of the stunting reduction acceleration program in Cirebon City.